Associations of inflammatory polyarthritis with clinical and radiological findings of temporomandibular disorders - Sari Oksanen; Kirsi Sipilä; Markku Heliövaara; Anna Liisa Suominen; Sisko Huumonen (Medical Journals Sweden, 2024)
Objective: To evaluate the association of different forms of inflammatory polyarthritis with clinical signs of temporomandibular disorders (TMD) and radiological findings in temporomandibular joint (TMJ), based on a nationwide health survey in Finland. The aim was also to assess the presence of clinical and radiological TMD findings in subjects with increased risk for developing rheumatoid arthritis (RA). Material and methods: Anationally representative sample included 6331 Finnish adults who participated in the Health 2000 Survey (BRIF8901). Subjects were examined for signs of TMD, findings in panoramic radiograph of TMJ, musculoskeletal health and serology (rheumatoid factor, RF, and anti-cyclic citrullinated peptide, aCCP). Results: Sixty-four percent of seronegative RAand 60% of seropositive RAsubjects had at least one sign of TMD. While adjusting for confounding factors (gender, age, dentures and smoking history), RAwas significantly associated with crepitation and abnormal radiological findings in TMJ. Seronegative RAwas also associated with restricted mouth opening. Systemic autoimmunity associated with RA("at risk of RA") was not associated with clinical or radiological TMD findings. Conclusions: Clinical and radiological findings of TMD are more prevalent among subjects with inflammatory polyarthritis than among the population in general in the Finnish adult population.